Occupational stress among technical teachers in technical school in Johore, Malacca and Negeri Sembilan - Yahaya, Azizi (2006)
This study investigated factors that contributed stress and the level of occupational stress among the technical teachers who are currently teaching in technical schools in Johore, Malacca and Negeri Sembilan. There were five teacher stress sources that included in this study: pupil misbehaviour, teacher workload, time and resources difficulties, interpersonal relationships, and recognition. A total of 92 teachers (N = 92) from nine technical schools in three states, which are Johore, Malacca and Negeri Sembilan were choosed randomly to represent the population by using the cluster over cluster method. The instrument for this study was adapted from the Teacher Stress Inventory constructed by Boyle, Borg, Falzon and Baglioni (1995) and had been modified by Mokhtar (1998) and Mazlan (2002). A pilot survey was done among 20 technical teachers in a technical school in Johore Bahru. The alpha croncbach for the instrument in this study was 0.982. The data were analyzed using both despcriptive (mean, frequency, and percentage) and inferency (Independent t-Test, Pearson Correlation, and One Way ANOVA) methods. Data analysis indicated that the overall stress level of respondent was moderate. Among the five stressors, pupil misbehaviour was the strongest determinant of teacher stress with a mean of 3.67. Other factors were teacher workload (mean = 3.00), time and resources difficulties (mean = 2.97), recognition (mean = 2.90), and interpersonal relationships (mean = 2.85) respectively. The workload and other factors had caused a moderate stress on the respondents. The results indicated that there was no significant difference of work stress among the respondent based on gender, marriage status, and highest academic qualification. Furthermore, the results were failed to indicate a significant correlation between teacher stress and demographic factors such as age, length of teaching experience, and the respondents’ monthly salary.